POLITENESS STRATEGIES BY TAYLOR SWIFT IN THE ELLEN SHOW - FEBRIANTI, FIKA; Ariana, Cindi Rizka (ELite Journal : International Journal of Education, Language and Literature, 2025)
This article discusses the politeness strategies used by Taylor Swift in her interview on The Ellen Show. This research aims to understand how Taylor Swift uses polite language to build social relationships, maintain a positive image, and deal with various situations during the interview. The approach used in this study is Brown and Levinson's politeness theory, especially on positive politeness and negative politeness strategies. The results show that Taylor Swift predominantly uses positive politeness. This strategy can be seen from the way she compliments Ellen, shares personal stories, and uses humor to create a warm and familiar atmosphere. These actions show respect and create closeness with the interlocutor and the audience. In addition, Taylor also uses negative politeness, especially when answering sensitive questions. This strategy helps her maintain privacy without appearing evasive, for example by using polite expressions or careful answers. This research shows that politeness strategies play an important role in creating effective communication, especially in the context of media interviews. By using this approach, Taylor Swift was able to maintain a good relationship with Ellen and her audience, while projecting a friendly and professional image. The findings provide insight into how celebrities use language strategies to build successful interactions.